Assessment of the bioaccessibility of phenolics from Australian grown lettuces by in vitro simulated gastrointestinal digestion and colonic fermentation. (August 2022) - Shi, Min; Wu, Hanjing; Li, Minhao; Liu, Ziyao; Duan, Xinyu; Barrow, Colin; Dunshea, Frank; Suleria, Hafiz A.R.
Abstract: Lettuce varieties are rich in phytochemicals with strong antioxidant properties, mainly due to the presence of many phenolic compounds. The health effects of these phenolic compounds are dependent on their bioaccessibility, bioavailability and bioactivities. This study aimed to evaluate the differences in the content and bioaccessibility of phenolic compounds in green lettuce (iceberg, baby cos, and green little gem) and red lettuce (red oak leaf, lollo rosso, and red little gem), their antioxidant properties and short chain fatty acids (SCFAs) production after in vitro gastrointestinal digestion and colonic fermentation. Lollo rosso showed the highest content of phenolic compounds (1.23 mg GAE/g) and flavonoids (0.36 mg QE/g), as well as the antioxidant capacities after gastrointestinal digestion. After colonic fermentation, only baby cos and red little gem showed significantly higher TPC (5.13 mg GAE/g) and TFC (1.95 mg GAE/g), respectively. Most phenolic compounds in lettuce were mostly bioaccessible after gastric and small intestinal digestion, except for the kaempferol which relied more on the colonic fermentation. However, high percentage of kaempferol still could be found in the colonic fermented residual, probably due to the presence of dietary fiber and the interactions with other components. All lettuce varieties achieved the peak production of SCFAs after 16 h, except iceberg which displayed the highest total SCFAs production just after 8 h fermentation. It could be inferred that the iceberg (green lettuce) could be more beneficial to gut health while lollo rosso (red lettuce) could contribute more antioxidant properties after consumption. Graphical abstract: Image 1 Highlights: Lollo rosso (red lettuce) showed higher concentration of phenolic compounds and remarkable antioxidant potential during gastrointestinal digestion. Most of detected phenolic compounds in lettuce were highly bioaccessible in the upper digestive tract while a significant amount of kaempferol still remained in colonic residue. Iceberg (green lettuce) showed higher phenolic bioaccessibility than all red lettuce. Iceberg showed the highest production of SCFAs among all varieties after 8 hours colonic fermentation which could be more beneficial to gut health after consumption.